Transendensi dalam Pemikiran Simone de Beauvoir dan Emmanuel Levinas - Pranowo, Yogie (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2016)
Simone de Beauvoir and Emmanuel Levinas are two of the leading philosophers who gave rise to the idea of transcendence. While for Beauvoir transcendence is a fully human effort (particularly among women) to come out of the shackles of patriarchal culture, for Levinas transcendence extends to a broader scope, that is, to humanism as well as to the relationships among people. Beauvoir would see transcendence as women’s efforts to break out of the structures of patriarchy through the three strategies it offers, viz., that women must work, engage in intellectual activities, and become perpetrators of action for the sake of social transformation. As for Levinas, transcendence is closely associated with human face. The face is not merely an object of intentional consciousness, but representing the significance of human transcendence. Through the face, one might recognise the presence of others. On the other hand, it shows the face of infinite dimensions in such a way that it cannot be subdued by the attempts of human consciousness willing to master it.